In-situ and real-time tests on the damage evolution and fracture of thermal barrier coatings under tension: a coupled acoustic emission and digital image correlation method - Zhou, M.; Yao, W.; Yang, X.; Peng, Z.; Li, K.; Dai, C.; Mao, W.; Zhou, Y.; Lu, Chunsheng (Elsevier S.A, 2014)
By using a coupled acoustic emission (AE) and digital image correlation (DIC) technique, the failure behavior of air plasma sprayed thermal barrier coatings (TBCs) was investigated. The in-situ DIC observations show that the characteristics of AE signals, extracted from the fast Fourier transform, are closely related to the failure modes of a TBC system, which was applied to real-time reveal its damage evolution during tension. It is shown that there is a typical power-law relationship between the vertical crack density in coating and strain in substrate. A damage variable defined as a function of the cumulative AE events can be used to characterize the different fracture stages of a TBC system. With the increase of strain in substrate, the AE-b value estimated by the Gutenberg–Richter law varies from 2.0 at the initial regime to a plateau value of 1.2.